Climate regulatory risks and corporate bonds - Lee Seltzer; Laura T. Starks; Qifei Zhu (Federal Reserve Bank of New York, 2022)
Investor concerns about climate and other environmental regulatory risks suggest that these risks should affect corporate bond risk assessment and pricing. We test this hypothesis and find that firms with poor environmental profiles or high carbon footprints tend to have lower credit ratings and higher yield spreads, particularly when their facilities are located in states with stricter regulatory enforcement. Using the Paris Agreement as a shock to expected climate risk regulations, we provide evidence that climate regulatory risks causally affect bond credit ratings and yield spreads. Accordingly, the composition of institutional ownership also changes after the Agreement.
Keywords: G38; G24; G00; 330; climate risk; regulatory risk; fixed income